Institute of Metals Division - Immobilization of Interstitial Carbon During the Purification of Iron in a Zone-Melter - B. F. Oliver; F. Garofalo (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1965)
Gas-metal heterogeneous reactions and zone-lrelting were sinultarneously employed to produce several high-purity irons with low interstitial contents in a levitating- zone melter. Successive zone-tneltitzg pusses were made in carious sequences of atmospheves which included prepuvified tank hy-drogeta, water vapor hydrogen, palladiuril-purified hydrogen, and vacuunm of 2 x 10-6 Torr. Different irons ranging in purity from 99.89 to 99.996 pct with residual curbon contents of 17, 8 to 10, and 3 to 5 ppm have been Drepared. No measuvable gradient in the residual carbon content was observed along the entire zone-melted length (6-10 in.) in I-ilz.-diameter bars. The absence of a carbon-concentration gradient in the solid indicates an apparent distvihution coefficient of 1, an unusual condition. Internal friction, solid-state extraction, and hot-hardness results indicate that the level of mobile carbon in a iron depends on the gas-metal heterogeneous reactions employed. Purification under an oxidizing atmosphere resulted in the immobilization of nearly all of the carbon present at leuels of 10 ppm or less. Continuation of purification in a reducing atmosphere veturued the carbon to a state of mobility which was aguin reversed by further purification in all oxidizing atmosphere. The immobilization of curbon at "vesidual levels " is believed to be associated with a strong interaction between carbon and oxygen atoms. frons with low carbon and nitrogen contetzts which did not exhibit a hot-hardness peak were produced after zone ynelting in vacuum. CARBON, nitrogen, and oxygen have strong and well-known effects on many properties of iron. These effects persist even at concentrations of 5 to 20 ppm. The intent of the present investigation was to establish procedures for the preparation of high-purity iron with concentrations of these elements in the range of 5 to 20 ppm and lower. The results reported here deal with the procedures employed to prepare high-purity iron, and with observations on the behavior of certain elements at "residual levels": particularly carbon. The details of the (levitating) zone melter in which the final purification steps are performed and the necessary control of the pertinent solidification variables have been described previously.1,2 MATERIALS AND PROCEDURES Commercial electrolytic iron was induction vacuum-melted and cast into 30-lb ingots. Melt additions and ingot analyses for carbon, oxygen, and nitrogen are noted in Table I. All ingots were melted in stabilized zirconia crucibles conditioned with one iron wash heat. Middle sections of the ingots were forged to 1-1/4-in. rounds, machined to 1-in.-diameter bars, then cut to 36-in. lengths. The zone-melting operations were performed on six iron bars (A to F) at a freezing velocity of 2 in. per hr with the freezing interface rotating2 at 200, 300, or 400 rpm. Liquid zones were passed through the bars in various sequences of atmospheres, Table 11, including prepurified tank H2, palladium-purified Hz, wet H2, and system vacuum of 2 x 1018 Torr. Wet-Hz atmospheres were obtained by bubbling palladium-purified Hz through water exhibiting a resistance of 3 megohms. This water was heated with a platinum-immersion heater and was degassed prior to use. Zone melting in a wet-HZ atmosphere resulted in oxidation of the elements which are oxi-dizable with respect to iron. Fine oxide particles were observed on the surface of the liquid zone, and were encased in the bar surface with the passage of the molten zone. Between each zone pass, the surface of the bar was removed by filing and deep etching; this was continued until the oxide formation ceased. The filings were magnetically separated and the residues analyzed by optical spectroscopy. These were especially high in silicon and manganese. Samples were removed from the iron bars, with few exceptions, following each zone-melting operation. A 0.08-in.-thick disc was cut with an Al2O3 cut-off wheel at a point 1/2 in. above the beginning of freezing. Material from each disc was used for hot-hardness measurements, resistivity-ratio measurements, and carbon, nitrogen, and oxygen analyses. Analyses for most other elements were